JURIDICAL ANALYSIS OF THE ROLE OF JUSTICE COLLABORATORS IN EFFORTS TO GROW PUBLIC PARTICIPATION TO DISCLOSE CRIMINAL ACTS OF NARCOTICS (Research Study at the National Narcotics Agency of the Riau Islands Province) - Febriandy, Boy; Dahlan, Dahlan; Parameshwara, Parameshwara (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The role of Justice Collaborator in Fostering Community Participation in Disclosure of Neglected Narcotics Crimes. In the Practical Operational Approach, especially the perpetrator's witnesses who cooperate in uncovering criminal acts, especially those involving organized syndicates, causing law enforcement in the field to act based on their own judgment, not based on clear and firm legal rules in determining the perpetrators of criminal acts. act as witnesses of cooperating perpetrators or other acts. with the aim of uncovering the actions of the drug syndicate network.